Periwayat Syiah dalam Ṣaḥīḥ al-Bukhārī - Husein, Alwi (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
The article reviews the existance of Shi’ite ḥadīth narrator with various levels, in which their report narrated in Sunni authoritative ḥadīth literature namely Ṣaḥīḥ al-Bukhārī. It attempts to examine the chain of transmission (sanad) in Ṣaḥīḥ al-Bukhārī with various classical and contemporary rijāl al-ḥadīth books, such as Ibn Abī Ḥātim (d. 327), Ibn Ḥibbān (d. 354), Yūsuf al-Mizzī (d. 742), al-Dhahabī (d. 748), Ibn Ḥajar (d. 852), al-Suyūṭī (d. 911), Muḥammad Nāṣir al-Dīn al-Albānī (d. 1420) and Shu’ayb al-Arna’ūṭ (d. 1438), to identify the Shia narrators reported in Ṣaḥīḥ al-Bukhārī. By using historical approach and hadīth narrators (rijāl al-Ḥadīth) analysis, the article finds thirty-two Shia narrators, and twenty-four Rāfiḍah narrators composed in Ṣaḥīḥ al-Bukhārī. That is because in methodological perspective, al-Bukhārī does not put beliefs and theological affiliations of the hadīth narrators as parameters for accepting or rejecting the hadīth.